PENGARUH PELAKSANAAN ANGGARAN BELANJA MODAL DAN KETAATAN PADA PERATURAN PERUNDANGAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH KOTA BANDA ACEH - Nurina, Nurina; Yahya, M. Rizal (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The research examines the effect of implementation of capital expenditure and adherence to laws and regulations on accountability performance of city agencies Banda Aceh. The research objective was to determine the effect of the implementation of the capital expenditure budget and compliance with laws and regulations to the accountability of the performance of city agencies Banda Aceh partial or collectively. The of this study was population treasurer of 30 working units in the city of Banda Aceh, which have 90 treasurer. Primary data were collected by distributing questionnaires. Data analysis used is multiple linear regression model. The results of the study can be explained that the implementation of the capital expenditure has positive influence on performance accountability of government agencies in Banda Aceh. Obedience to the laws and regulations has positive effect on performance accountability of government agencies in Banda Aceh. The correlation between the variable capital expenditure budget implementation and compliance with laws and regulations with the accountability of the performance of city agencies Banda Aceh is positive and relatively strong. The role of variable capital expenditure budget implementation and compliance with laws and regulations with the accountability of the performance of city agencies Banda Aceh is still more dominant than the other variables.Keywords The implementation of the capital budget, adherence to the rule of law, accountability of the performance of government agencies